RNAi-based functional analysis of a theta-class glutathione S-transferase implicated in deltamethrin detoxification in Pardosa astrigera (Araneae: Lycosidae) - Li, Rui; Jiao, Liyalin; Zhai, Shuxin; Jin, Xingjie; Cui, Congcong; Ren, Boqi; Zhang, Xinghua; Shen, Fangyu; Ma, Min; Rieger, Michael A.; Li, Xinmin (Frontiers in Physiology, 2025)
IntroductionGlutathione S-transferases (GSTs) play a critical role in insecticide detoxification. This study investigates the molecular characteristics and biological function of a theta-class glutathione S-transferase gene, PaGSTt1, in the spider Pardosa astrigera.MethodsBased on transcriptome data, the PaGSTt1 gene (GenBank accession number: PV848051.1) was cloned using RT-PCR and characterized via bioinformatics analysis. Its expression patterns across different developmental stages (2nd to 6th instar nymphs and adults), tissues (cephalothorax, abdomen, and legs), and in response to deltamethrin exposure (LC10, LC30, LC50) were quantified by RT-qPCR. RNA interference (RNAi) was employed to knock down PaGSTt1 in male spiders, and the subsequent change in susceptibility to deltamethrin was evaluated.ResultsThe PaGSTt1 gene contains a 678 bp open reading frame encoding 225 amino acids. Expression was detected at all developmental stages, with the highest level in 5th instar nymphs. In adults, expression was highest in the abdomen and was generally higher in males than in females. Deltamethrin exposure significantly induced PaGSTt1 expression: at LC10 (5.151 mg/L), upregulation occurred at 6 h and 48 h; at LC30 (8.619 mg/L), induction was observed at 48 h; and at LC50 (12.311 mg/L), significant upregulation was detected at 6 h, 24 h, and 48 h. RNAi successfully silenced PaGSTt1, reducing its expression by 78.69% after 24 hours. This knockdown led to a 34.54% increase in mortality in male spiders exposed to LC30 deltamethrin compared to the dsGFP control group.DiscussionThe findings demonstrate that PaGSTt1 is inducible by deltamethrin and that its knockdown significantly increases mortality in P. astrigera, indicating its important role in the detoxification of this insecticide. This suggests that PaGSTt1 contributes to pesticide tolerance mechanisms in this species.